'God Is Protecting Me … And I Have Mace': Defensive Labour In Precarious Workplaces. (6th September 2021) - Ladegaard, Isak; Ravenelle, Alexandrea J; Schor, Juliet
Abstract: Since the 1970s, welfare cuts and market deregulation have made jobs increasingly precarious and workers have been made responsible for their own safety. In this context, technological developments have recently paved the way for the gig economy, in which tasks and services are distributed on digital platforms. Drawing on interviews with 32 Uber and Lyft drivers in New York City and Boston, we document how the intersecting forces of precarity, responsibilization and organizational innovation spawn the need for 'defensive labour', that is, emotional and cognitive self-protective practices.